2008
DOI: 10.1002/jmv.21111
|View full text |Cite
|
Sign up to set email alerts
|

Presence of tropical spastic paraparesis/human T‐cell lymphotropic virus type 1‐associated myelopathy (TSP/HAM)‐like among HIV‐1‐infected patients

Abstract: A total of 38 HIV-1/HTLV-1 co-infected subjects were identified in this cohort: Twenty-six had already been diagnosed with AIDS and 12 remained asymptomatic. Six of 38 co-infected subjects (18%) were diagnosed as having TSP/HAM and also AIDS, and for 5 of them TSP/HAM was their first illness. One additional incident case was diagnosed after 2 years of follow-up. No modifications on HIV-1 viral load was seen. In contrast, the co-infected with TSP/HAM-like group showed higher HTLV-1 proviral load (505 +/- 380 vs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
12
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 27 publications
1
12
1
Order By: Relevance
“…19 Casseb et al diagnosed HAM/TSP in six out of 38 (18%) dually infected patients and found that HTLV-1 proviral loads were significantly higher in patients with HAM/TSP compared to asymptomatic co-infected patients (p = 0.012). 20 Our study confirms a high frequency of HIV co-infection in patients with HAM/TSP in KwaZulu-Natal. Dual infection is associated with a younger age of clinical presentation and shorter duration of symptoms prior to presentation.…”
Section: Discussionsupporting
confidence: 83%
“…19 Casseb et al diagnosed HAM/TSP in six out of 38 (18%) dually infected patients and found that HTLV-1 proviral loads were significantly higher in patients with HAM/TSP compared to asymptomatic co-infected patients (p = 0.012). 20 Our study confirms a high frequency of HIV co-infection in patients with HAM/TSP in KwaZulu-Natal. Dual infection is associated with a younger age of clinical presentation and shorter duration of symptoms prior to presentation.…”
Section: Discussionsupporting
confidence: 83%
“…A higher incidence of myelopathy among HIV1/HTLV-1 coinfected subjects has been previously reported21 but was not a feature here. Coinfection with HIV-2 was found in only 2/8.…”
Section: Discussioncontrasting
confidence: 45%
“…The results indicated that 73% of the coinfected patients and 16% of the patients infected with only HIV-1 developed myelopathy [100]. Another group reported that the prevalence of HAM/TSP among HTLV-1/HIV-1-coinfected patients in Brazil was 8% [101]. Schutte and coworkers [102] observed in a cohort of patients in Pretoria, South Africa, that HTLV-1/HIV-1-coinfected individuals were prone to developing HAM/TSP at an earlier age than when infected with HTLV-1.…”
Section: Incidence Of Ham/tsp Among Htlv-1/hiv-1-coinfected Patientsmentioning
confidence: 98%
“…Furthermore, the period of time in which the coinfected patients remained asymptomatic was shorter than the monoinfected patients (less than 3 years) [102]. Furthermore, Casseb and colleagues [101] demonstrated that the levels of HTLV-1 proviral DNA load in coinfected patients with HAM/TSP were five times higher than in asymptomatic coinfected individuals. HTLV-1 proviral DNA levels in PBMCs varied during the course of HTLV-1 infection [103].…”
Section: Incidence Of Ham/tsp Among Htlv-1/hiv-1-coinfected Patientsmentioning
confidence: 99%